2021
DOI: 10.22456/1679-9216.109254
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine-Tiletamine-Zolazepam Followed by Inhalant Anesthesia in Spectacled Bears (Tremarctos ornatus)

Abstract: Background: The spectacled bear (Tremarctos ornatus) is the only bear species inhabiting South America and is classified as vulnerable according to the International Union for Conservation of Nature (IUCN) Red List. Among the few publications on the use of general anesthesia and advanced monitoring of ursids in veterinary hospital settings, little is described regarding chemical restraint, general anesthesia and monitoring of spectacled bears. This case series describes the use of a dexmedetomidine-tiletamine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However McEntire et al (2020) reported that in 146 anesthetic procedures performed in three species of bears including the spectacled bear, the maintenance of the anesthesia, in most cases, was completed with isoflurane e ketamine and in just three cases propofol was used, given as an intravenous bolus. Garofalo et al (2021) used a dose of 2.0 mg/kg of propofol for anesthetic induction in a spectacled bear premedicated with tiletamine-zolazepam (3.8 mg/kg) and dexmedetomidine (6.4 µg/kg).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However McEntire et al (2020) reported that in 146 anesthetic procedures performed in three species of bears including the spectacled bear, the maintenance of the anesthesia, in most cases, was completed with isoflurane e ketamine and in just three cases propofol was used, given as an intravenous bolus. Garofalo et al (2021) used a dose of 2.0 mg/kg of propofol for anesthetic induction in a spectacled bear premedicated with tiletamine-zolazepam (3.8 mg/kg) and dexmedetomidine (6.4 µg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the protective reflection and develop chewing of the animal, the propofol 1% (Propovan-Cristália, Sao Paulo, Brazil) was administered slowly (4.0 mg/kg/IV) (1.81 mg/lb), followed by tracheal intubation using a number 12 cuffed tube (Solidor, Well Lead Medical co., Ltd, China) as shown in Figure 2. Maintenance of anesthesia was performed by using a portable inhalation anesthesia machine (Incotec; Espirito Santo, Brazil) in a circuit with rebreathing using a flexible corrugated trachea with a diameter of 22 mm, using isoflurane in 100% of free oxygen at a flow rate of 50 mL/kg/min as reported by Garofalo et al (2021) , during two hours, monitored with the support of AxiumVet© software program (IMFtec, Sao Paulo, Brazil), which was also used to measure heart rate (HR), electrocardiogram (ECG), respiratory rate (RR), pulse oximetry (SpO 2 %) and temperature (To) (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations